Theoretical Approach to the Labor Skills of International and Latin American University Graduates: A Systematic Review - Navarro, David Ricardo Castro; Seclén, Gustavo Adolfo Ventura; Navarro , Maria Alejandra Castro (Journal of Ecohumanism, 2024)
The main objective of this study was to establish the number of scientific studies published in Wos, Scopus and Scielo from 2021 to 2023 regarding the variety of labor skills a defined group of university graduates had. For this purpose, a systematic review or research was generated, based on the findings of the aforementioned repositories, the main results of which were the low existence of theories related to the variables of study, being a consequence of the selection of empirical articles, it was also determined that the dimensions found in the selected scientific production were the skills of foreign language use, technology management and professionalization. It was also possible to conclude, based on the number of scientific articles found in Wos and Scopus, that, as a main conclusion, the formation of the university towards the graduate, as well as the profile that they created in an institutional way, affect, to a great extent, their potential labor skills.